And the monkey learned nothing : dispatches from a life in transit - Lutz, Tom (Sightline books: The Iowa series in literary nonfiction, 2016)
"Tom Lutz is on a mission to visit every country on earth. And the Monkey Learned Nothing contains reports from fifty of them, most describing personal encounters in rarely visited spots, anecdotes from way off the beaten path. Traveling without an itinerary and without a goal, Lutz explores the Iranian love of poetry, the occupying Chinese army in Tibet, the amputee beggars in Cambodia, the hill tribes on Vietnam's Chinese border, the sociopathic monkeys of Bali, the dangerous fishermen and conmen of southern India, the salt flats of Uyumi in Peru, and floating hotels in French Guiana, introduces you to an Uzbeki prodigy in the market of Samarkand, an Azeri rental car clerk in Baku, guestworkers in Dubai, a military contractor in Jordan, cucuruchos in Guatemala, a Pentecostal preacher in rural El Salvador, a playboy in Nicaragua, employment agents in Singapore specializing in Tamil workers, prostitutes in Colombia and the Dominican Republic, international bankers in Belarus, a teacher in Havana, border guards in Botswana, tango dancers in Argentina, a cook in Suriname, a juvenile thief in Uruguay, voters in Guyana, doctors in Tanzania and Lesotho, scary poker players in Moscow, reed dancers in Swaziland, young camel herders in Tunisia, Romanian missionaries in Macedonia, and musical groups in Mozambique. With an eye out for both the sublime and the ridiculous, Lutz falls, regularly, into the instant intimacy of the road with random strangers"--